EFFECT OF SHADE LEVEL ON GROWTH AND YIELD OF ONION PLANTS FROM SEED - Abdul Hadid; Febriana Febriana (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
The purpose of this study was to determine the effect of shade level on the growth and yield of shallot plants from seed. This research was conducted in Lolu Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi Province. The time of this research is from January to March 2021. This research was conducted using a Randomized Block Design (RAK) which consists of 5 levels of shade, namely N0 = No Shade, N1 = 9% Shade, N2 = 18% Shade, N3 = 38% Shade and N4=Shade 50%. Each treatment was repeated 3 times so that there were 15 experimental units. Parameters observed were plant height, number of leaves, number of tillers per clump, number of tubers per cluster, tuber circumference, fresh weight of tubers per cluster, weight of tuber per tile, tuber weight per ha and weather variables. The data obtained from the study were then analyzed using analysis of diversity (ANOVA). If the results of the diversity analysis show a real or very real influence, then it is continued with the Honest Significant Difference (BNJ) test at 5% level. The results of this study showed that the level of shade had a significant effect on the observed variables of tuber fresh weight, tuber weight and tuber weight per hectare, but on the variables of plant height, number of leaves, number of tillers, number of tuber clumps and tuber circumference had no significant effect. The 18% shade gives the best shallot crop yields.